Indonesian Childfree Women: Negotiating Women’s Autonomy and Patriarchal Ideology in Childfree-Short Movie - Ida Rosida; Sulhizah Wulan Sari; Tuty Handayani (Leksema: Jurnal Bahasa dan Sastra, 2026)
This article discusses complexities faced by modern Indonesian spouse named Alif and Kevin that portrays the childfree choices within their marriage presented in Childfree-Short Movie (2024), an Indonesian short film that was produced by Valencia and released on YouTube. This research aims to show the gap between women’s autonomy and patriarchal ideology through the narratives of the short movie engaging with the discourse of becoming childfree. This is qualitative research by employing the concept of gender and postfeminism. The result shows that the woman character named Alif, confirmes her life’s decision through a negotiation of the cultural expectations and traditional beliefs by expressing women's voices to gain freedom to have children. This leads Alif to negotiate her autonomy in the patriarchal ideology that must place her to be a mother. The text analysis is showing how the decision of becoming childfree woman in Indonesian culture are regarded as deviating to woman's roles, childfree women are considered selfish, unfulfilled, and disobedient gender norms. The issue of economics or financial capability   is also becoming the significant factor that the spouse decided themselves to be childfree particularly in the modern young spouse. The image of a childfree woman in Childfree-Short Movie is seen as a resistance toward traditional standards and a challenge of  societal expectations, notably about the notion of motherhood. Despite the short movie continually emphasizing the prevalent media representation of a childfree woman in Indonesia in the current year, women's choices remain incompatible with the Indonesian traditions and norm.